PERTIMBANGAN HAKIM DALAM MENJATUHKAN PUTUSAN PEMIDANAAN PERKARA KEKERASAN BERSAMA-SAMA TERHADAP ORANG - Dimey Cantika Ardinata; Bambang Santoso (Sebelas Maret University, 2025)
This article analyzes the judge's consideration in deciding the crime of joint violence against persons. The purpose of this article is to find out whether the judge's consideration in imposing a punishment decision is in accordance with the provisions of the Criminal Procedure Code, especially Article 183 of the Criminal Procedure Code. This research is a prescriptive and applied normative legal research with a case approach, namely examining one case of joint violence against persons with the Decision of the Surakarta District Court Number: 202/Pid.B/2023/PN.Skt. The collection of legal materials is carried out by means of literature studies in the form of primary legal materials and secondary legal materials. The analysis technique is to use the deductive syllogism method. Based on this research, it is found that in the case of joint violence against persons, the judge in handing down the verdict is in accordance with the provisions of Article 183 of the Criminal Procedure Code so that the defendant can be convicted. Translated with DeepL.com (free version).